Intention to Visit Tourist Destinations: The Effect of Using Mobile Tourism Recommender System on Visit Intention by Using TTF Aspects, Technological Features, and Social Motivation - Suryana Setiawan; Nilamsari Putri Utami; Mohammed Al Kwarizmi Dwi Anggara; Muhamad Raihan Fikriansyah; Muhammad Daril Nofriansyah; Rania Azzahra; Achmad Nizar Hidayanto (Faculty of Computer Science Universitas Indonesia, 2022)
This study aims to determine whether the use of the MTRS application can affect the intention to visit tourist destinations and the level of influence of the factors that can influence it. The model in this study involves the Task-Technology Fit (TTF) model and aspects, technological features, social motivation, visit intention, and use intention to identify visit intention. The method used to collect data in this research is a web-based online survey using Google Forms distributed through social media. The target respondents were individuals who had used the mobile tourism recommender system. Data from 213 valid respondents were processed and analyzed using Structural Equation Modeling (SEM) with the help of the SmartPLS application. The conclusion is that the use of the MTRS application can affect the intention to visit tourist destinations.